Perancangan Aplikasi Rekapitulasi Temuan Keuangan dan Administrasi pada Perangkat Daerah Berbasis Web Studi Kasus: Inspektorat Daerah Kabupaten Lebak - Mohamad Shihab Awalun Nurhayat; Dani (CV. Shofanah Media Berkah, 2025)
The recap of financial and administrative findings at the Regional Inspectorate of Lebak Regency was previously done manually using methods like Excel and Word, making data updates and reporting challenging. This study designs a web-based application using PHP and JavaScript to facilitate financial and administrative monitoring within the Regional Apparatus Organizations of Lebak Regency. The research employs a prototype software development model, including requirements analysis, system design, implementation, testing, and maintenance. The application was tested using Black Box Testing to ensure that its primary functions work correctly. User satisfaction was evaluated using the End User Computing Satisfaction (EUCS) method, with the majority of the 20 user samples achieving an average score of 4.2/5.0 on the Likert scale, indicating high satisfaction. Field testing results in Muara Village and Cilangkap Village in Wanasalam District showed increased efficiency in inputting follow-up actions from the monitoring results. Before the application was used, on July 2, 2024, Muara Village had only completed 2 recommendations, but by July 16, 2024, this number had increased to 7 recommendations. In Cilangkap Village, 9 recommendations were successfully completed on July 25, 2024. The application successfully improved the efficiency and effectiveness of managing the Follow-Up Monitoring Results (TLHP) and the Regional Government Financial Statements (LKPD), and received positive feedback from users, demonstrating a significant improvement in financial monitoring and administrative processes in Lebak Regency.